Risk factors for dental caries in Latin American and Caribbean countries - Stefania MARTIGNON; Angelo Giuseppe RONCALLI; Evelyn ALVAREZ; Vicente ARÁNGUIZ; Carlos Alberto FELDENS; Marília Afonso Rabelo BUZALAF (Sociedade Brasileira de Pesquisa Odontológica, 2021)
Abstract Identifying the risk factors for dental caries is vital in epidemiology and clinical practices for developing effective preventive strategies, both, at the individual and collective levels. Different causality/determination models have been proposed to understand the development process of dental caries. In the present review, we designed a model inspired by the world-known social determinants models proposed in the 90s and more recently in the 10s, wherein the contextual factors are placed more externally and encompass the individual factors. The contextual factors included those related to the cultural and societal values, as well as the social and health government policies. The individual factors were classified into the following categories: socioeconomic (social class, occupation, income, and education level), demographic characteristics (age, sex, and ethnicity), behavioral factors (non-use of fluoride dentifrice, sugar consumption, poor oral hygiene, and lack of preventive dental care), and biological factors (recent caries experience/active caries lesions, biofilm retentive factors, developmental defects of the enamel, disabilities, saliva amount and quality, cariogenic biofilm). Each of these variables was addressed, while focusing on the current evidence from studies conducted in Latin American and Caribbean countries (LACC). Based on the proposed model, educational aspects were addressed, and individual caries risk assessment and management decisions were proposed; further, implications for public health policies and clinical practice were described. The identification of modifiable risk factors for dental caries should be the basis for multi-strategy actions that consider the diversity of Latin American communities.